Internal Electronic Information as a Competitiveness‐Enhancing Resource in German Automotive Industry Suppliers1. (20th January 2016) - Bakos, Alexander; Miller, Christopher; Packham, Gary; Pickernell, David; Thomas, Brychan
Abstract : In German automotive industry suppliers, internal electronic information (IEI) satisfies the requirements of being a competitiveness‐enhancing resource.